Experimental investigation of the delignification process influence on thermochemical and kinetic properties of biomass - Maia, Amanda Alves Domingos; Enriquez, Yemall Alexander Maigual; de Morais, Leandro Cardoso [UNESP] (Springer Nature, 2020)
The study of biomass is extremely important, aiming to discover the potential of alternative source that are capable of promoting the development of new technologies. The thermal behavior and chemical characteristics of the Capsicum waste from the use for the manufacture of sauces and condiments were investigated using thermogravimetric analysis, higher heating values, ignition (Ti) and burnout temperatures (Tb) and kinetic study using isoconversional models. Torrefaction and pyrolysis conditions were applied. Characterization based on ultimate and proximate analysis, gravimetric and gravimetric yield factor were also realized. Thermal analysis showed a biomass conversion between 150 °C and 500 °C. Proximate analysis identified an average volatile content of 46.5%, and carbon and fixed carbon were 22.3 and 31.1%, respectively. Gravimetric yield varied between 28 and 58%. Considering the intersection model, ignition and burnout temperature varied between 342–354 °C and 470–503 °C, respectively. The deviation model found an ignition temperature between 210 and 249 °C. Biomass proved to be a possible source of biofuel with a significant economic potential.
Keywords: Combustion; Isoconversional methods; Kinetic study; Pyrolysis; Thermochemical conversion; Torrefaction